Analisa Optimisme Atitude Management pada Profil Website PT. Link Pasific Logistic - Fitri Anekawati (Port Management and Maritime Administration Journal, 2025)
This study aims to determine the attitude of the company in the fields of cargo, shipping, and port operations at PT. Link Pacific Logistic. The company's attitude can be analyzed through the presentation of the company's profile in describing its objectives and vision to be achieved. The main attraction lies in the company's introduction, which plays an important role in establishing a network of professional collaboration. In this analysis, the researcher has identified three types of attitudes: Permanence – the extent to which the company perceives achievements and challenges as temporary or long-lasting. Pervasiveness – the extent to which the company considers an event to impact the entire operational aspects or only certain areas.Personalization – the extent to which the company attributes successes and challenges to internal or external factors. Based on the research findings, the company's profile presentation shows very significant results, with permanence being the most dominant aspect in describing the company's objectives. ocial media interaction (source credibility, source homophily, and content quality) positively impacts future intention.